A strong heritability of psoriatic arthritis over four generations--the Reykjavik Psoriatic Arthritis Study - Karason, Ari; Love, Thorvardur Jon; Gudbjornsson, Bjorn (Rheumatology, 2009)
Objective. We have studied the prevalence of PsA in Reykjavik, Iceland, in a population-based cohort, and using the Icelandic genealogy database we have estimated the risk ratio (RR) spanning five generations. Methods. The national identification numbers of all 220 living Icelanders in Reykjavik known to have PsA were linked with the genealogy database. RRs for developing PsA were estimated in first-degree relatives (FDRs) to fifth-degree relatives of PsA cases. The kinship coefficient (KC) for PsA was also calculated. The control populations were 1000 and 10 000 sets of matched Icelandic subjects for each proband, respectively. Results. FDRs to fourth-degree relatives of patients with PsA had RRs of 39, 12, 3.6 and 2.3, respectively (all P -values < 0.0001), reflecting a strong genetic component, whereas the fifth-degree relatives had an RR of 1.2 ( P = 0.236). KCs of 5.0, 3.4, 1.7, 1.3, 1.0, 0.8 and 0.7 were observed for the first seven excluded meioses (all P -values < 0.0001), confirming the familial risk. Conclusions. Patients with PsA in Reykjavik, Iceland, are significantly more related to each other than to randomly sampled control subjects. This is in agreement with previous reports, but the present study examines the inheritance in more distantly related individuals. These findings indicate that in addition to a strong and complex genetic component in PsA, there is an important environmental contribution.